“Heroes” and “Villains” of World History across Cultures - Hanke, Katja; Liu, James H.; Sibley, Chris G.; Paez, Dario; Gaines, Stanley O., Jr.; Moloney, Gail; Leong, Chan-Hoong; Wagner, Wolfgang; Licata, Laurent; Klein, Olivier; Garber, Ilya; Böhm, Gisela; et al. (PLOS ONE, 2015)
Emergent properties of global political culture were examined using data from the World History Survey (WHS) involving 6,902 university students in 37 countries evaluating 40 figures from world history. Multidimensional scaling and factor analysis techniques found only limited forms of universality in evaluations across Western, Catholic/Orthodox, Muslim, and Asian country clusters. The highest consensus across cultures involved scientific innovators, with Einstein having the most positive evaluation overall. Peaceful humanitarians like Mother Theresa and Gandhi followed. There was much less cross-cultural consistency in the evaluation of negative figures, led by Hitler, Osama bin Laden, and Saddam Hussein. After more traditional empirical methods (e.g., factor analysis) failed to identify meaningful cross-cultural patterns, Latent Profile Analysis (LPA) was used to identify four global representational profiles: Secular and Religious Idealists were overwhelmingly prevalent in Christian countries, and Political Realists were common in Muslim and Asian countries. We discuss possible consequences and interpretations of these different representational profiles.